Cerebellar Lipo Neurocytoma: Case Report and Review of the literature - Uddin, Nasir; Karim, Rabiul; Rana, Sumon; Hojaifa; Sarker, Asit Chandra; Islam, Md Shafiqul; Hasan, Md Motasimul; Sikder, Md Shahidur Rahman (Bangladesh Journal of Neurosurgery, 2023)
Background: Cerebellar liponeurocytoma is a rare tumor of the central nervous system occurring mainly in the posterior fossa, which shows divergent glioneuronal differentiation and lipidized neoplastic cells and has been considered as a distinct clinicopathological entity. Case: Herein, we describe a 19-year-old male patient who presented to the hospital complaining of headache, nausea with balance difficulty. MRI revealed a contrast enhancing midline lesion of posterior fossa. After tumor resection, histological examination and immunohistochemistry were done and the diagnosis of cerebellar liponeurocytoma was confirmed. Conclusion: Liponeurocytoma is a rare benign tumor with cerebellum is the typical site for it. The therapy of choice is surgery. Postoperative radiotherapy has to be discussed individually. Bang. J Neurosurgery 2022; 12(1): 37-40